(untitled) (Citizenship in Action: Extension and Culture Magazine, 2025)
Sexually Transmitted Infections (STIs) are health issues that considerably affect young people. Therefore, this group represents a key population in the prevention of these infections, and it is the health network’s responsibility to reach them specifically. The present paper has as its theme the STI prevention actions carried out by ISTeja Prevenido Collective in locations not covered by health units’ actions such as bars, nightclubs, and parties/events attended by young people and the LGBTQIA+ population. The objective was to contribute to the policies of public health care services concerning the prevention of STIs. Two actions were developed in 2022: at the Gaymada event and Moonlight nightclub, both aimed at the LGBTQIA+ public. The Collective’s participation in the Gaymada event happened with a stand where it presented itself. The principal manners of STI prevention were reinforced to the present public and artists. It also counted the distribution of internal and external condoms, lubricants, self-tests for HIV, and informational pamphlets on STI prevention, including where to seek specialized help. In the Moonlight nightclub, the guidelines given to the population focused on HIV/AIDS prevention, using casual language and costumes by the members. Both objected to obtaining the approximation and acceptance of the present public. In addition, the distribution of informative materials, self-tests for HIV, condoms, and condom holders was realized, with the installation of boxes containing condoms in the establishment’s bathrooms. As a result of these activities, the approached public in both events showed interest in the theme, maintaining dialogues with the members during the actions. People assimilated the relevance of condom distribution and were clarified regarding its correct use, discussed STIs without taboo, and carried out the self-test for HIV as a form of prevention and, consequently, health conservation. The public contemplated in the Gaymada action was approximately 50 people, while the event in Moonlight reached around 150 individuals. Health education actions focused on preventing STIs must be part of preventive actions aimed at young people. Expanding these actions to different spaces with multiple approaches is essential for resolving public health issues, such as STIs spread. By being available in usually neglected and judged locations, the collective enables an exchange of experiences. Additionally, members can relate theory and practice, benefiting themselves - through improving their skills and knowledge - and the population through access to quality information and supply of materials for infection prevention. Finally, there is an expansion of the possibility of reaching younger people that sometimes do not seek health services.